THE EFFECT OF DIFFERENT IRRIGATION LEVELS ON THE GROWTH AND PHYSIOLOGY OF DATE PALM OFFSHOOT LEAVES - AL-Alwani, Haderr Abd-Alkadhim Hamza (Journal for Technology and Science, 2026)
Objective: Water is the most crucial factor that limits growth and yield of date palm, mainly in the arid and semi-arid areas. The focus of the current work has been on the assessment of the impact of various irrigation treatments on growth and physiological traits of date palm (Phoenix dactylifera L.) offshoot leaves. Method: Three irrigation treatments corresponding to optimal, medium, and deficit water supply were applied. The relative water content, chlorophyll content, and photosynthetic efficiency were also conducted on the growth traits including leaf area, fresh weight, and dry weight. The two phenological stages were applied on two irrigation regimes and our findings found that there was a significant effect of watering regime on growth and physiological traits of date palm offshoot leaves. Results: Growth were promoted and physiological performance were improved by moderate IR, and severe water deficit stress led to dramatic decreases in chlorophyll content, leaf water status, and photosynthesis. Physiological efficiency increased by irrigation but by marginal amounts. Novelty: These results highlight the significance of tailored irrigation strategies to improve the water use efficiency and sustainable production of date palm in water-scarce environments.